Aspectos morfológicos e ecológicos da ginodioicia em Dasyphyllum brasiliense (spreng.) Cabrera (Barnadesioideae, Asteraceae) - Lopes, Bruna Palese Thies (2017)
Dasyphyllum brasiliense has two sexual systems: monoecious and gynodioecious, being the studied population characterized as gynodioecy, constituted by complete and pistilated individuals. The evolution of this system depends on the influence of the medium on the morphology and biology of the different floral types. Studies that unite these areas are extremely important in understanding the evolution of gynodioecy. In this way, the objective of this work was to compare the floral morphology, the development of stamens / staminodes and ecological aspects in a population of the species. The different individuals have clear differences in flower size and morphology. Floral pieces are larger in whole individuals except stigma, which has larger lobes, in addition to containing more trichomes and a wider degree of aperture. The anthers of complete flowers have common development for the family and the abortion in the other morph occurs during the development of the parietal layers, what establishes these individuals like pistillates. The complete individuals have a greater diversity of floral visitors, but the species that participates most in pollination in both is Apis melifera. Through these data and phenology, which shows a higher percentage of phenophases in complete individuals in the population, it can be thought that these have a greater advantage over the others, but the pistillates individuals occur in greater numbers in the population, a fact that must have relation with the high predation of the seeds, probably due to attractiveness such as greater floral size and presence of pollen grains as food resources. This predation is part of the evolutionary process, allowing the population control, in order to keep the individuals pistillates. Thus, the theory of resource allocation can be established in the evolutionary process of the species.